EFFECT OF BEAUTY VLOGGER TESTIMONIAL (REVIEW) ON CONSUMER INTEREST (VIEWERS) ON COSMETIC PRODUCTS - Rizka - Agustiara; Mari - Okatini; Aam Amaningsih Jumhur (Politeknik Negeri Semarang, 2019)
This study aims to (1) identify and explain the effect of beauty vlogger testimonials on consumer interest (2) know and explain consumer interest (viewers) on cosmetic products. This type of research is explanatory research with a quantitative approach. The variables of this study include Beauty Vlogger, and consumer interest in cosmetic products. Population criteria in this study were cosmetic users of Madame Gie with a minimum age of 17 who had watched one of the Beauty Vlogger Fatya Biya riviewers, who used Madame Gie products and had bought Madame Gie products. Samples used in this study were 116 respondents taken using purposive sampling and data collection methods using a questionnaire indirectly (online) with the format of the goole form. Analysis of the data used is descriptive statistical analysis and path analysis. The data in this study were processed using SPSS 22 for Windows. The results of the path analysis show that the Beauty Vlogger's testimonial (riview) has a significant effect on Consumer Interests, Consumer Purchase Intention to have a significant effect on product purchases